Recyclable catalyst for the asymmetric Henry reaction based on functionalized imidazolidine-4-one-copper(II) complexes supported by a polystyrene copolymer. Issue 45 (4th November 2015) - Harmand, Lydie; Drabina, Pavel; Pejchal, Vladimír; Husáková, Lenka; Sedlák, Miloš
Graphical abstract: Abstract: Imidazolidine-4-one derivatives were anchored by the thiol-ene click reaction to a swellable pearl-like polystyrene copolymer and their complexes with Cu(II) acetate were utilized as recyclable heterogeneous catalysts for the Henry reaction of substituted aldehydes with nitromethane. The corresponding 2-nitroethanols were mostly obtained in high yields (65–99%) and with enantioselectivities of up to 92% ee. After a fivefold recycling of the catalyst, the decrease in enantioselectivity was negligible (Δ 3% ee).